Pumped hydro storage plants: a review - Vilanova, Mateus Ricardo Nogueira [UNESP]; Flores, Alessandro Thiessen [UNESP]; Balestieri, José Antônio Perrella [UNESP] (Springer Nature, 2020)
Pumped hydro storage plants (PHSP) are considered the most mature large-scale energy storage technology. Although Brazil stands out worldwide in terms of hydroelectric power generation, the use of PHSP in the country is practically nonexistent. Considering the advancement of variable renewable sources in the Brazilian electrical mix, and the need to provide flexibility to the national electrical system, several official documents cite PHSP as an important alternative for the expansion of the Brazilian electrical system. This article presents the state of the art of PHSP and its use, in order to create a theoretical basis for future research on the subject, also providing theoretical support for Brazilian energy planning. The review includes a global panorama on the use of PHSP in the world, the technical and projective foundations on this type of technology, its benefits, and disadvantages, in addition to the new configurations and possible layouts for the construction of pumped hydro storage plants. Finally, the challenges and trends for the dissemination of PHSP technology are addressed.
Keywords: Energy storage; Hybrid renewable energy systems; Pumped hydro storage plants; Renewable energy integration